Pupuk Berbasis Mikroalga: Fungsi, Aplikasi, dan Prospek Pasar dalam Pertanian Organik - Datia Siti Nur Lisa; Aida Nursidah; Hani Susanti (Buitenzorg: Journal of Tropical Science, 2026)
Microalgae exhibit high biodiversity and are found in various habitats, including agricultural soil. The intensification of agriculture by chemical fertilizers results in significant environmental problems, including water pollution, accumulation of xenobiotic chemicals, diminished soil quality and fertility, and adverse effects on human health. Organic farming is highlighted as an effective approach to mitigate these problems. Microalgae offer key functions in agriculture as biostimulants, biofertilizers, biocontrol agents, sources of phytohormones, and soil moisturizers. These roles indicated the importance of microalgae in sustainable and organic agriculture, particularly for CO2 sequestration, nutrient recycling from waste streams, and enhancing crop tolerance to abiotic stress. This review discusses practical application methods, field challenges, sustainable water sources for microalgae biomass production, market trends for biofertilizers made from this biomass, and long-term sustainability factors to establish safety and standardization protocols to ensure their reliability. Microalgae biomass can be produced in photobioreactors or open ponds and applied to agricultural land as wet inoculum, dry biomass, or extracted metabolites. Integration with irrigation and hydroponic systems offers additional potential for efficient nutrient delivery. The global market for microalgae fertilizer is projected to expand significantly due to increasing awareness of sustainable farming and rising demand for organic food. These fertilizers are eco-friendly, reduce nutrient waste and soil degradation, and are suitable for organic crop production as they are natural and free from synthetic chemicals or GMOs. In conclusion, microalgae represent sustainable and effective strategies to enhance soil fertility, stimulate plant growth, and strengthen crop protection in organic farming.   Keywords: biocontrol agents, algal biomass, circular bioeconomy, commercial viability, abiotic stress mitigation